Application Of Digital Signal Processing In Echo Cancellation : A Survey - Jalaputhra, Dewakumari; Hashim, Nik Mohd Zarifie; Ibrahim, Mohd Izhan; Ja'afar, Abd Shukur; Salleh, Azahari; Mohamad, Najmiah Radiah (IJSEA, 2014)
-